Influence of probiotic bacterium Lactobacillus acidophilus on the survival and growth of pearl oyster Pinctada fucata spat - Subhash, S K; Lipton, A P; Paulraj, R (Indian Journal of Fisheries, 2011)
Combination of micro-alga Chaetoceros calcitrans and the probiotic bacterium Lactobacillus acidophilus evaluated at 1:1 and 1:2 levels revealed that in the probiotic treated group, Pinctada fucata spat registered significantly high survival of 79.7 and 89.0 % (P